2020
DOI: 10.5853/jos.2019.03048
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Stem Cell Therapy after Ischemic Brain Injury

Abstract: Stem cells have been used for regenerative and therapeutic purposes in a variety of diseases. In ischemic brain injury, preclinical studies have been promising, but have failed to translate results to clinical trials. We aimed to explore the application of stem cells after ischemic brain injury by focusing on topics such as delivery routes, regeneration efficacy, adverse effects, and <i>in vivo</i> potential optimization. PUBMED and Web of Science were searched for the latest studies examining stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
66
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 188 publications
0
66
0
3
Order By: Relevance
“…Many preclinical and clinical studies have reported therapeutic effects of stem cells in ischaemic brain injury, ischaemic heart failure, and limb ischaemia [ 8 , 9 , 10 , 11 , 12 , 13 ]. Although stem cell therapies have been shown to have numerous advantages over conventional therapies, their feasible translation is hindered by many factors, including the isolation of stem cells (especially stem cells derived from the bone marrow, embryo, and umbilical cord), the inability to control differentiation after administration, immunological rejection, tumour formation, inappropriate stem cell migration, the viability of cells after administration, and the limited understanding of how stem cells work in vivo [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many preclinical and clinical studies have reported therapeutic effects of stem cells in ischaemic brain injury, ischaemic heart failure, and limb ischaemia [ 8 , 9 , 10 , 11 , 12 , 13 ]. Although stem cell therapies have been shown to have numerous advantages over conventional therapies, their feasible translation is hindered by many factors, including the isolation of stem cells (especially stem cells derived from the bone marrow, embryo, and umbilical cord), the inability to control differentiation after administration, immunological rejection, tumour formation, inappropriate stem cell migration, the viability of cells after administration, and the limited understanding of how stem cells work in vivo [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell treatment demonstrates apparent beneficial effects in preclinical stroke models by reducing infarct size and improving behavioral and histological deficits [ 9 , 10 , 11 ]. Furthermore, preclinical experimentation has established that stem cell therapies are effective days after the ischemic stroke event, allowing for an extension of the therapeutic window for stroke treatment [ 11 , 12 ]. Despite the potential of stem cell therapy established in preclinical stroke models, there exists a frustrating disconnect between results when translated to clinical experimentation [ 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-ischemic brain tissue is characterized by a pro-inflammatory environment that prevents stem cells from establishing and inducing neuroregeneration [ 13 ]. Thus, combinate administration with different biomaterials and drugs has been analyzed with the aim of improving stem cell transplantation [ 12 , 13 ]. Biomaterials have gained particular interest due to the great variety of molecular compositions and their roles in recovery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They explored the regeneration efficacy of neural stem cells and introduced methods to optimize cell-based therapies. Due to some limitations related to the usage of neural stem cells, application of other pretreated cell types can also be beneficial for the ischemic brain [ 2 ]. Our research group has been studying the regenerative potential of epidermal neural crest stem cells (EPI-NCSCs) derived from hair follicles of rat and human since 2013 [ 3 , 4 ].…”
mentioning
confidence: 99%